Design and Build a Website-Based Mechanic Information System in Bangkinang City (Analysis System) - Nurfajri Naldo; Hanantatur Adeswastoto; Novi Yona Sidratul Munti (Journal of Engineering Science and Technology Management, 2021)
In this day and age, information technology is increasingly developing and supporting the presentation of information quickly and precisely. It can be known that in the business world, information systems have become an important part of a company and organization. Therefore, a company and an organization are very dependent on the information and knowledge possessed, because with the strength of a company and organization we can see. With the existence of information systems in various fields of companies and other industries, making a company / industry become developed. An example of one of the businesses in the automotive sector, such as a workshop, can develop by using an information system as one of its business strategies. The increasing number of motor vehicle users today, competition in business the workshops are also increasing. Such as service facilities that come to the place where vehicle users are located to provide ease of use of service facilities through the creation of web-based applications.